Association between asthma, obesity, and health behaviors in African American youth. (2nd April 2020) - Nagy, Matthew R.; McGlumphy, Kellye C.; Dopp, Richard; Lewis, Toby C.; Hasson, Rebecca E.
Abstract: Background: There is a clear relationship between obesity and asthma, with obesity recognized as a risk factor for asthma. There is mounting evidence, however, that asthma may predict obesity risk via behavioral pathways. Objectives: The purpose of this study was to assess the cross-sectional relationships between asthma, body mass index (BMI) percentile, and behavioral factors including caloric intake, dietary inflammatory index, moderate-vigorous physical activity (MVPA), and sedentary time (SED) among African American adolescents. Methods: A community-based sample of 195 African American youth (ages 11–18 years) were included in this analysis. Asthma status was based on self-report using the International Study of Asthma and Allergies in Children's Phase Three questionnaire. MVPA and SED were measured via accelerometry, and caloric intake and dietary inflammatory index were evaluated with the Food Frequency Questionnaire. Weight status was assessed via BMI percentile using measured weight, height, and CDC growth charts. Results: Adolescents with a history of asthma were significantly more overweight (62% vs. 43%, p = 0.04) and consumed a higher inflammatory diet (1.6 ± 0.3 vs. 1.0 ± 0.2, p = 0.02) than their peers who never had asthma. After adjusting for all covariates, activity and dietary variables, odds ratio analysis revealed adolescents who reported ever having asthma were 3.1 ± 1.5 times as likely to be overweight or obese than adolescents with no asthma history ( p = 0.02). Conclusions: Presence of asthma history was associated with increased obesity risk in African American adolescents, independent of behavioral factors. Longitudinal studies are needed to better understand the relationship between asthma and obesity in African American adolescents.